Early Labor Market Prospects and Family Formation - Mattias Engdahl; Mathilde Godard; Oskar Nordström Skans (Institute of Labor Economics (IZA), 2019)
We use quasi-random variation in graduation years during the onset of a very deep national recession to study the relationship between early labor market conditions and young females' family formation outcomes. A policy-pilot affecting the length of upper-secondary vocational tracks allows us to compare females who graduated into the onset of the Swedish financial crisis of the 1990s to those graduating during the final phase of the preceding economic boom while netting out the main effect of the policy. We find pronounced, but short-lived, negative labor market effects from early exposure to the recession for low-grade students in particular. In contrast, we document very long-lasting effects on family formation outcomes, again concentrated among low-grade students. Young women who graduated into the recession because of the policy-pilot formed their first stable partnerships earlier and had their first children earlier. Their partners had lower grades, which we show to be a strong predictor of divorce, and worse labor market performance. Divorces were more prevalent and the ensuing increase in single motherhood was long-lasting. These negative effects on marital stability generated persistent increases in the use of welfare benefits despite the short-lived impact on labor market outcomes. The results suggest that young women respond to early labor market prospects by changing the quality threshold for entering into family formation, a process which affects the frequency of welfare-dependent single mothers during more than a decade thereafter.
Keywords: E32; I26; J12; J13; J22; J31; 330; cost of recessions; female labor supply; family formation